Chest HRCT versus RT-PCR for the Detection of COVID-19 in Bangladesh (Jalalabad Medical Journal, 2025)
The coronavirus disease 2019 (COVID-19) pandemic is a crisis of a completely different magnitude, and it is a challenge to life in the whole world, including Bangladesh. The real-time reverse transcription polymerase chain reaction (RT-PCR) tests are currently the gold standard diagnostic tool for COVID-19. This observational study was done to evaluate the diagnostic assessment of high-resolution computed tomography (HRCT) of the chest as compared to a RT-PCR test in COVID-19 patients attending the Radiology and Imaging department of Jalalabad Ragib-Rabeya Medical College Hospital, Sylhet, from 1st July 2020 to 31st December 2021. This study included 387 patients admitted to the ICU and suspected of having COVID-19 who went to the radiology and imaging department for HRCT of the chest for the diagnosis of COVID-19 pneumonia. Simultaneously, nasal swabs from the same number of patients were tested by RT-PCR in the government-approved centre to diagnose COVID-19. Demographic and clinical data were collected by a structured questionnaire, and analysis was done with the help of the Statistical Package for Social Science (SPSS) version 23. Abnormal HRCT was discovered in 317 patients, 309 of whom were positive and 8 of whom were negative by RT-PCR. The difference between the two groups was statistically significant (p